The G-patch domain of Mason-Pfizer monkey virus is a part of reverse transcriptase - Křízová, Ivana; Hadravová, Romana; Štokrová, Jitka; Günterová, Jana; Doležal, Michal; Ruml, Tomáš; Rumlová, Michaela; Pichová, Iva (Journal of virology, 2012)
Mason-Pfizer monkey virus (M-PMV), like some other betaretroviruses, encodes a G-patch domain (GPD). This glycine-rich domain, which has been predicted to be an RNA binding module, is invariably localized at the 3' end of the pro gene upstream of the pro-pol ribosomal frameshift sequence of genomic RNAs of betaretroviruses. Following two ribosomal frameshift events and the translation of viral mRNA, the GPD is present in both Gag-Pro and Gag-Pro-Pol polyproteins. During the maturation of the Gag-Pro polyprotein, the GPD transiently remains a C-terminal part of the protease (PR), from which it is then detached by PR itself. The destiny of the Gag-Pro-Pol-encoded GPD remains to be determined. The function of the GPD in the retroviral life cycle is unknown. To elucidate the role of the GPD in the M-PMV replication cycle, alanine-scanning mutational analysis of its most highly conserved residues was performed. A series of individual mutations as well as the deletion of the entire GPD had no effect on M-PMV assembly, polyprotein processing, and RNA incorporation. However, a reduction of the reverse transcriptase (RT) activity, resulting in a drop in M-PMV infectivity, was determined for all GPD mutants. Immunoprecipitation experiments suggested that the GPD is a part of RT and participates in its function. These data indicate that the M-PMV GPD functions as a part of reverse transcriptase rather than protease.
Keywords: Animals; Cell Line; Humans; terciární struktura proteinů; lidé; RNA-Directed DNA Polymerase; zvířata; buněčné linie; Polyproteins; Protein Structure, Tertiary; Mason-Pfizer monkey virus; reverzní transkriptasa; Masonův-Pfizerův opičí virus; polyproteiny; Viral Proteins; virové proteiny